MiR-191 as a Key Molecule in Aneurysmal Aortic Remodeling - Sabina Lichołai (MDPI AG, 2021)
Abdominal aortic aneurysms (AAA) are a complex disease with an unclear pathomechanism. A positive family history is emphasized as a significant risk factor, and a nonspecific model of inheritance suggests participation of epigenetic regulation in the pathogenesis of this disease. Past studies have implicated microRNAs in the development of AAA; therefore in this project, we measured miR-191 levels in AAA patients and compared them with a control group. We found that miR-191 levels were significantly elevated in aneurysmal patients, although this did not correlate with the available clinical data. We then developed an in vitro model where, using cells with an endothelial phenotype, we determined the effect of miR-191 on the transcriptome using RNA sequencing. Subsequent pathway analysis established that some of the perturbations mediated by miR-191 can be explained by several processes which have long been observed and described in literature as accompanying the development of abdominal aortic aneurysms.